Intelligent Design and the First Amendment: A Response - Jay D. Wexler (Washington University Law Review, 2006)
In late 2004, the school board of the Dover School District in Pennsylvania passed a series of measures requiring teachers to inform students that evolution is incomplete and to make available to students a textbook on “intelligent design” (“ID”), a purportedly scientific theory suggesting that an intelligent agent created the universe and everything in it, including human beings. In December 2005, a federal district Judge ruled that the school’s policies violated the First Amendment. In a series of recent writings, including a full length book and several articles, Baylor University professor Francis J. Beckwith has argued that public schools may constitutionally teach ID. I disagree with Beckwith’s ultimate conclusion that teaching ID in the public schools would likely be constitutional. In my view, teaching the theory would raise significant problems under the First Amendment. More specifically, I disagree with Beckwith in three important substantive areas, namely whether courts should find that ID constitutes a religious belief, whether the Court’s decision in Edwards v. Aguillard casts doubt on the constitutionality of teaching ID, and whether teachers have any First Amendment academic freedom right to teach ID in direct contravention of clear school policy. In this three-part Article I address these issues in turn.
Keywords: Intelligent design (Teleology); Academic freedom; Establishment clause (Constitutional law); Public schools